Selective polycarboxylation of semiconducting single-walled carbon nanotubes by reductive sidewall functionalization - Gebhardt, Benjamin; Hof, Ferdinand; Backes, Claudia; Müller, Matthias; Plocke, Thomas; Maultzsch, Janina; Thomsen, Christian; Hauke, Frank; Hirsch, Andreas (Journal of the American Chemical Society, 2011)
The efficient and controllable synthesis, the detailed characterization, and the chemical postfunctionalization of polycarboxylated single-walled carbon nanotubes SWCNT(COOH) are reported. This innovative covalent sidewall functionalization method is characterized by (a) the preservation of the integrity of the entire σ-framework of SWCNTs; (b) the possibility of achieving very high degrees of addition; (c) control of the functionalization degrees by the variation of the reaction conditions (reaction time, ultrasonic treatment, pressure); (d) the identification of conditions for the selective functionalization of semiconducting carbon nanotubes, leaving unfunctionalized metallic tubes behind; (e) the proof that the introduced carboxylic acid functionalities can serve as versatile anchor points for the coupling to functional molecules; and (f) the application of a subsequent thermal degradation step of the functionalized semiconducting tubes leaving behind intact metallic SWCNTs. Functional derivatives have been characterized in detail by means of Raman, UV-vis/nIR, IR, and fluorescence spectroscopy as well as by thermogravimetric analysis combined with mass spectrometry, atomic force microscopy, and zeta-potential measurements. © 2011 American Chemical Society.